The Daily You How the New Advertising Industry Is Defining Your Identity and Your Worth - Joseph Turow (Yale University Press, 2012)
At the start of the twenty-first century, the advertising industry is guiding one of history’s most massive stealth efforts in social profiling. At this point you may hardly notice the results of this trend. You may find you’re getting better or worse discounts on products than your friends. You may notice that some ads seem to follow you around the internet. Every once in a while a website may ask you if you like a particular ad you just received. Or perhaps your cell phone has told you that you will be rewarded if you eat in a nearby restaurant where, by the way, two of your friends are hanging out this very minute. You may actually like some of these intrusions. You may feel that they pale before the digital power you now have. After all, your ability to create blogs, collaborate with others to distribute videos online, and say what you want on Facebook (carefully using its privacy settings) seems only to confirm what marketers and even many academics are telling us: that consumers are captains of their own new-media ships. But look beneath the surface, and a different picture emerges. We’re at the start of a revolution in the ways marketers and media intrude in—and shape—our lives. Every day most if not all Americans who use the internet, along with hundreds of millions of other users from all over the planet, are being quietly peeked at, poked, analyzed, and tagged as they move through the online world. Governments undoubtedly conduct a good deal of snooping, more in some parts of the world than in others. But in North America, Europe, and many other places companies that work for marketers have taken the lead in secretly slicing and dicing the actions and backgrounds of huge populations on a virtually minute-by-minute basis. Their goal is to find out how to activate individuals’ buying impulses so they can sell us stuff more efficiently than ever before. But their work has broader social and cultural consequences as well. It is destroying traditional publishing ethics by forcing media outlets to adapt their editorial content to advertisers’ public-relations needs and slice-and-dice demands. And it is performing a highly controversial form of social profiling and discrimination by customizing our media content on the basis of marketing reputations we don’t even know we have.